Androgen receptor as a potential therapeutic target in castration-resistant prostate cancer: a bibliometric analysis (2005–2024) - Jiexiang Zhang; Weichen Yuan; Tongtong Zhang; Xuesong Liu; Dongliang Xu (Discover Oncology)
Abstract Introduction The androgen receptor (AR) remains a focal target in castration-resistant prostate cancer (CRPC) research, with recent studies providing valuable insights for advancing AR-targeted therapies. This study employs bibliometric methods to comprehensively analyze research trends in the CRPC and AR fields, identifying emerging hotspots and future directions. Methods Publications from 2005 to 2024 were extracted from the Web of Science Core Collection (WoSCC). Bibliometric analysis and data visualization were performed using VOSviewer, CiteSpace, and the R package “Bibliometrix.” Results A total of 3,149 publications authored by 15,704 researchers across 75 countries were analyzed. Publication output exhibited rapid growth over the past two decades. The United States dominated contributions, with the University of Washington ranking as the leading institution. Antonarakis, Emmanuel S. was the most prolific author, while Scher, Howard I. emerged as the most cited researcher. PROSTATE published the highest number of studies, whereas CANCER RESEARCH was the most cited journal. References co-citation analysis and keyword burst revealed persistent research emphasis on AR splice variants and CRPC drug resistance, with emerging investigations into novel membrane antigens representing current frontiers. Conclusion This study delineates the evolving knowledge framework and shifting priorities in CRPC and AR research, offering strategic insights to guide future AR-targeted therapeutic development for CRPC.